The Influence Of Career Development And Work Environment On Employee Job Satisfaction (Case Study of Employees at PT. Singa Terbang Dunia) - Stefani Ita; Giri Nurpribadi (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
Human resources (HR) are the most important factor in efforts to achieve the success of organizations, groups and individuals. Seeing the importance of human resources, companies or organizations need to pay attention to their employees in career development and work environment to achieve maximum employee job satisfaction. This research is survey research with a quantitative approach. The population of this study was employees of PT. The flying lion of the world. Data collection used questionnaires while data analysis was done using multiple regression analysis. Findings from structural models have proven that almost all hypothetical relationships are proven to be supported. There is a positive influence of partial career development on employee job satisfaction, there is a positive influence of the partial work environment on employee job satisfaction and there is also a simultaneous influence of career development and work environment on employee job satisfaction. Keywords: Career Development, Work Environment, Employee Job Satisfaction.